Size-dependent deposition of inhaled nanoparticles in the rat respiratory tract using a new nose-only exposure system. Issue 1 (2nd January 2016) - Buckley, Alison; Hodgson, Alan; Warren, James; Guo, Chang; Smith, Rachel
ABSTRACT: Concerns about the potential health effects of exposure to nanomaterials have led to a growing number of in vivo inhalation toxicity studies using nanoparticle aerosols. Estimates of aerosol deposition within the respiratory tract are important for these studies to enable: (a) the interpretation of the results, in particular, the evaluation of dose–response relationships; (b) comparison with the results of other related studies; and (c) the extrapolation of results from animal models to human. Unfortunately, only a limited number of studies have been undertaken to investigate respiratory tract deposition efficiencies for nano-sized aerosol particles. This is of particular importance as deposition efficiencies are predicted to vary significantly over the nano-size range for some elements of the respiratory tract. In this study, female Wistar-Kyoto rats were exposed in a new design nose-only inhalation exposure system to spark generated radioactive iridium-192 nanoparticle aerosols of four particle sizes chosen to cover the majority of the nano-size range (nominal sizes: 10, 15, 35, and 75 nm). The content of iridium-192 in the lung, head, gastrointestinal tract, and various other organs and tissues was measured. Aerosol deposition efficiencies in the whole respiratory tract and components (head airways, lung, alveolar region, and tracheobronchial region) were estimated and compared with the predictions of the Multiple Path Particle Dosimetry (MPPD) model (v2.11). The experimentally derived deposition efficiencies were broadly consistent with, but typically higher than, model predictions and the results of comparable studies in the literature. Copyright © 2016 American Association for Aerosol Research